DETECTING ERRORS IN ENGLISH MADE BY INTERMEDIATE INDONESIAN LEARNERS OF ENGLISH IN ENGLISH DEPARTMENT STUDENTS OF STAIN PAREPARE - Kaharuddin Kaharuddin (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2016)
This research is constructed from a descriptive method to describe an aspect of second language acquisition that is systematic errors made by language actors in the speech of second language. The data were collected from picture description tasks and interviews to delineate error categories made by Indonesian learners of English. The results of this study show that grammatical errors are found in the four major errors categories. The most frequent errors occur in verb tense (33.8 %) followed by errors in article usage (17.5%) then errors in using preposition (14.1%) the next, errors produced in verb agreement (13.1%) and then, errors detected in noun ending (6.2%) and the last, errors committed in word order and sentence structure (1.9%).